The Shape of Herodotean Rhetoric : A Study of the Speeches in Herodotus' Histories with Special Attention to Books 5-9 - Zali, Vasiliki (International Studies in the History of Rhetoric Ser, 2014)
Contents -- Acknowledgements -- Abbreviations -- Note on Text and Translations -- Introduction -- Part 1 Architectonics of Speech -- Chapter 1 Allocation of Speech -- 1.1 Modes of Analysis -- 1.2 Greek vs. Greeks -- 1.3 Speech and Power/Authority -- 1.4 Greeks vs. Persians -- Part 2 Speech and Competition -- Chapter 2 Debates -- 2.1 General Observations -- 2.2 Language -- 2.3 On the Cusp between Homer and Thucydides -- 2.4 Test Cases -- Part 3 Speech and Typology -- Chapter 3 Alliance Speeches -- 3.1 Literary Tradition and Early Rhetorical Handbooks -- 3.2 Alliance Motifs in Herodotus -- 3.3 Test Cases -- 3.4 Persian Alliances: An Overview -- Chapter 4 Pre-Battle Speeches -- 4.1 The Genre of Pre-Battle Exhortation -- 4.2 Exhortation and Exhortatory Motifs in Literature and Rhetoric -- 4.3 Herodotean Harangues -- 4.4 Function of Exhortations: Case Studies -- 4.5 Harangues and Herodotean Narrative -- Conclusion -- Appendix 1 -- Appendix 2 -- Bibliography -- Index of Passages Cited -- General Index.